Utilization of Uterine and Umbilical Artery Doppler in the Second and Third Trimesters to Predict Adverse Pregnancy Outcomes: A Nigerian Experience - Ademola J. Adekanmi; Adebola Roberts; Imran O. Morhason-Bello; Abiodun O. Adeyinka (Mary Ann Liebert, 2022)
Objective: To assess the utility of uterine and umbilical artery Doppler in the second and third-trimester in predicting adverse pregnancy outcomes. Methodology: In a prospective longitudinal study, the demographic, clinical, Doppler ultrasound parameters of the uterine and umbilical arteries of 84 consecutive women attending the antenatal clinic at 22?24 weeks and 116 women at 30?34 weeks gestation and pregnancy outcomes were documented and analyzed. Results: Pregnant women with adverse pregnancy outcomes had significantly higher second-trimester mean uterine systolic/diastolic (S/D) ratio (p?=?0.001), pulsatility index (PI; p?=?0.003), umbilical artery S/D (p?=?0.016), and resistivity index (RI; p?=?0.041) as well as higher third-trimester uterine S/D and PI. While pregnancies with adverse fetal outcomes showed significantly higher uterine artery S/D and PI at the second trimester, third-trimester uterine showed higher S/D, RI, and PI and umbilical artery PI than in women with normal fetal outcomes. The combination of uterine PI and early diastolic notch were predictors of maternal outcomes and correctly predicted 73% (p?<?0.001) in the second trimester. By the third trimester, the uterine PI alone was the best predictor and accurately predicted about 62% of maternal outcomes (p?=?0.028). In addition, the second-trimester uterine S/D and early diastolic notch and uterine PI in the third trimester correctly predicted 79% and 78% of fetal outcomes, respectively. Conclusion: Among unselected pregnant women population, the second-trimester Doppler parameters are better predictors of maternal adverse pregnancy outcomes, while adverse fetal outcome prediction by uterine and umbilical Doppler at the second- and the third-trimester parameters are comparable.